The Effect of Revenue Sharing Funds, Capital Expenditure, and Local Own Source Revenue on Economic Growth in the Bakorwil 1 Madiun Region - Saputra, Fahiya Ardi; Hutabarat, Ruth Eviana (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the effect of Revenue Sharing Funds, Capital Expenditures, and Local Own-Source Revenues on Economic Growth. This study uses a quantitative approach utilizing panel data sourced from the Ministry of Finance and the Central Statistics Agency (BPS). The analysis was conducted to assess the extent to which local fiscal variables contribute to economic growth dynamics in the Bakorwil 1 Madiun region. The results show that Revenue Sharing Funds have a significant positive effect on economic growth, indicating that an increase in the allocation of revenue sharing funds can boost regional economic activity. Meanwhile, capital expenditure has a significant negative effect on economic growth, suggesting that the effectiveness of capital expenditure is not yet optimal. Finally, Local Own-Source Revenue has been proven to have a significant positive effect, indicating that regional fiscal capacity through the utilization of local own-source revenue can strengthen economic growth. These findings emphasize the importance of effective regional fiscal management to support sustainable regional economic development.